2013
DOI: 10.1007/s10719-013-9500-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the candidacy of LPS-based glycoconjugates to prevent invasive meningococcal disease: conjugates based on core oligosaccharides

Abstract: In this study we have prepared glycoconjugates with core oligosaccharides (OS) from the lipopolysaccharide (LPS) of Neisseria meningitidis, thus avoiding the neo-epitopes of the deacylated lipid A region of the derived LPS molecule identified in our previous studies. A comprehensive investigation was performed with glycoconjugates prepared from the most extended to the most truncated core OS still maintaining the conserved inner core epitope. As previously, we have established reproducible bactericidal killing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The LPS core Dpgm mutant closely resembles the synthetic tetrasaccharide 1 (Figure 1). Increased antibody binding to these mutants is in accordance with observations made in earlier immunization studies with detoxified LPS core glycoconjugates that revealed strongest reactivity to homologous strains (Cox et al, 2010a;St Michael et al, 2014). …”
Section: Chemistry and Biologysupporting
confidence: 89%
See 1 more Smart Citation
“…The LPS core Dpgm mutant closely resembles the synthetic tetrasaccharide 1 (Figure 1). Increased antibody binding to these mutants is in accordance with observations made in earlier immunization studies with detoxified LPS core glycoconjugates that revealed strongest reactivity to homologous strains (Cox et al, 2010a;St Michael et al, 2014). …”
Section: Chemistry and Biologysupporting
confidence: 89%
“…Deacylation and incorporation of functional groups for covalent linkage to carrier proteins are performed on purified LPS prior to conjugation but generate neoepitopes that may elicit nonspecific antibodies (Cox et al, 2010a(Cox et al, , 2010bSt Michael et al, 2014). Furthermore, purified LPS offers a limited possibility for antigen refinement due to its restriction to sequentially expressed LPS core structures on engineered knockout mutants.…”
Section: Chemistry and Biologymentioning
confidence: 99%
“…The above narration of the chemical methods points to the fact that glycoconjugation of chosen sugars on to proteins and other biomolecules has emerged as an important area of research. Unexpected immune response to the linker connecting the sugar epitope with the carrier protein can be a serious impediment, as illustrated with LPS-based vaccine development against wild-type meningococcal bacterial strain (St. Michael et al, 2014 ). Whereas the conjugation methods are well-developed, site selectivity issues are highly demanding, and many methods lack the ability to conjugate the sugars at a pre-determined site, for example, in a protein with several lysine sites.…”
Section: Discussionmentioning
confidence: 99%
“…Also, recent preclinical glycoconjugate vaccine candidates had reflected an increased awareness that the steric hindrance arising from directly conjugating carbohydrate to a carrier protein would require a linker or spacer to evade. At the same time, different linkers may also result in varied immunogenicity [115]. In this section, chemical conjugation methods used for past clinical and preclinical LPS-based vaccine candidates are discussed.…”
Section: Chemical Conjugation Methodsmentioning
confidence: 99%
“…The reduction of these Schiff intermediates via the addition of borate buffer generates stable glycoconjugates. The addition of linkers, such as adipic acid dihydrazide (ADH), can be incorporated in reductive amination to evade steric hindrance and facilitate coupling of protein to the sugar component [115,120].…”
Section: Reductive Aminationmentioning
confidence: 99%